Ion Track Nanolithography Using Thick Cross-Linked Poly(methyl methacrylate) 950 Photoresist - Koukharenko, Elena; Jekaterina , Kuleshova; Fowler, Marcel; Kok, Swee Leong; Tudor, Michael J.; Beeby, Stephen P.; Nandhakumar, Iris; White, Neil (Jpn. J. Appl. Phys., 2010)
This study shows that poly(methyl methacrylate) (PMMA) 950 thick photoresist is a promising polymer for ion-track nanolithography templates for nanomaterials fabrication resulting in high aspect ratio nanostructures ranging from 100 to 500 with highly selective etch rates when using deep ultraviolet (DUV) cross linking polymerisation prior to the ion-track irradiation. DUV exposure times and post exposure hardbake conditions are crucial factors for achieving high aspect ratio structures. Exposure doses of 6600 mJ/cm2 with post exposure hardbake at 180 °C for 90 s gave promising preliminary results for high aspect ratio nanotemplates using thick layer of PMMA 950 photoresist.